ANALISIS KEMISKINAN RUMAH TANGGA MELALUI FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI KECAMATAN TUGU KOTA SEMARANG - Yufi Halimah Sa’diyah; Fitrie Arianti (Diponegoro Journal of Economics, 2012)
ABSTRACT This study aims to analyze household poverty through the factors that influence in the District of Tugu of Semarang city. The factors are including education,  family size, and asset. The research was conducted in the District of Tugu to the number of households in the district of Tugu as many as 1530 families, with a sample of 94 families. There are 3 variables under study, namely: education, family size, and asset. The instrument of data collection used questionnaires and interviews. Analysis of the data used is Ordinary Least Square (OLS) using instrument of SPSS 16.0. The results showed that the variables of education and capital have a significant positive impact on household poverty. While the family size variables have a significant negative impact on household poverty.